Freestanding thin film and its manufacturing method
Patent Information
- Application Number
- JP2021214186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-12-28
Smart Images

Figure 0007645788000003 
Figure 0007645788000004 
Figure 0007645788000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a free-standing thin film having an apatite structure and a method for producing the same. [Background technology]
[0002] Electrochemical cells used in fuel cells and the like have a single cell structure in which a cathode and an anode are arranged with an electrolyte membrane sandwiched therebetween. Zirconia-based oxides such as stabilized zirconia and perovskite-type oxides are known as oxide ion conductors that serve as electrolyte membranes. In recent years, apatite-type compounds, which have excellent oxide ion conductivity, have been attracting attention. Apatite-type compounds have a hexagonal crystal structure, and it is expected that, for example, by providing orientation, the movement of oxide ions will be facilitated and ion conductivity will be increased.
[0003] For example, Patent Document 1 discloses a substrate-oriented apatite-type complex oxide film composite having an oriented apatite-type complex oxide on a substrate, and a method for producing the same. The oriented apatite-type complex oxide is a lanthanum silicate-based complex oxide, and is formed on a substrate as a film having a thickness of more than 0.5 μm and not more than 5 μm and an orientation degree of 0.6 or more as determined by the Lotgering method. The substrate is a metal, alloy, ceramic, or a composite material thereof, and the amorphous complex oxide formed on the substrate is heat-treated in an atmosphere of a predetermined oxygen partial pressure or less to crystallize it into an apatite structure and impart orientation. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6088715 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, a composite oxide of a desired composition is prepared in advance, and then formed on a substrate by, for example, sputtering, and heat-treated to form a composite of an oriented apatite-type composite oxide film and a substrate. Although this method is said to be free of restrictions on the substrate material, there are restrictions on bonding with functional materials such as electrodes, and the desired cell structure is not necessarily obtained. For example, in order to form a dense body to be used as an electrolyte membrane for an electrochemical cell, it is desirable for the substrate to also be dense, and therefore it is difficult to use a porous body that functions as the cathode or anode of an electrochemical cell as a substrate.
[0006] On the other hand, there are also electrolytes used in electrochemical cells that are produced as free-standing films that are not supported by a substrate or the like, and then electrodes are formed on both end faces. Such free-standing electrolytes are made of single crystals of apatite-type composite oxides formed by, for example, the Czochralski method, and are thinned by polishing, but in order to avoid the occurrence of cracks due to polishing, the thickness has traditionally been limited to about 50 μm. In addition, there are methods for obtaining thinner plate-like crystals, such as the flux method, but it is difficult to increase the crystal size.
[0007] The present invention has been made in view of the above problems, and has an object to provide a free-standing thin film made of a composite oxide having an apatite structure and having a free-standing thin film shape with a larger area, and a method for producing the same. [Means for solving the problem]
[0008] One aspect of the present invention is A self-supporting thin film (1) made of an apatite-type composite oxide, The apatite-type composite oxide has one or more polycrystalline layers (11) in a film thickness direction (Z) in which crystal particles (C) of the apatite-type composite oxide are aggregated in a film plane direction (X, Y) with their grain boundaries (C1) in contact with each other; The membrane thickness t is 0.2 μm or more and 5.0 μm or less, and the membrane area S is 1.0 cm 2 The film is a free-standing thin film having a surface roughness Rz of 20 nm or less.
[0009] Another aspect of the invention is a method for producing a free-standing thin film, comprising the steps of: forming a first layer (300) made of a composition that is sublimable at the crystallization temperature of the apatite-type composite oxide on the surface of the substrate (200); forming an amorphous complex oxide film (100) having the same constituent elements as the apatite-type complex oxide on the surface of the layer of the composition; forming a second layer (400) made of an oxide or a precursor thereof containing a part of the constituent elements of the apatite-type complex oxide on the surface of the amorphous complex oxide film; and forming the polycrystalline layer made of the apatite-type complex oxide by heating the amorphous complex oxide film to a temperature equal to or higher than the crystallization temperature thereof and removing the first layer by sublimation. Effect of the Invention
[0010] The free-standing thin film of the above configuration is composed of a polycrystalline layer made up of crystal grains of apatite-structured composite oxide, and it is believed that the numerous crystal grain boundaries that separate the grains improve the film strength and contribute to maintaining the thin film shape. In addition, the film surface roughness Rz is 20 nm or less, and the film surface is flat with little unevenness, which is thought to alleviate stress concentration due to surface unevenness and maintain the film strength. As a result, when the film area S is 1.0 cm 2 It is presumed that the above-mentioned thin film can be maintained in a state where it is not supported by a substrate or the like.
[0011] Such a free-standing thin film can be manufactured by the method shown in the other embodiment above. That is, a first layer made of a composition that can be sublimated by heat treatment is formed on a substrate in advance, and the first layer is sublimated and removed during heat treatment to crystallize apatite, so that the free-standing thin film can be separated from the substrate. It is also presumed that by forming a second layer containing the constituent elements of apatite on an amorphous complex oxide film and performing heat treatment, the constituent elements of apatite are diffused when the amorphous complex oxide film crystallizes, improving the orientation in the film thickness direction and reducing the unevenness of the film surface. This allows the crystal grain boundaries to grow in the film thickness direction while controlling the crystal growth behavior, and allows the production of a free-standing thin film with a larger area than conventional ones.
[0012] As described above, according to the above aspect, it is possible to provide a free-standing thin film made of a composite oxide having an apatite structure and having a free-standing thin film shape with a larger area, and a method for producing the same. In addition, the symbols in parentheses described in the claims and the means for solving the problems indicate a correspondence with the specific means described in the embodiments described below, and do not limit the technical scope of the present invention. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is an overall perspective view showing a schematic configuration of a free-standing thin film in a first embodiment. [Diagram 2] FIG. 2 is a diagram showing a schematic crystal structure of an apatite-type complex oxide constituting a free-standing thin film in the first embodiment. [Diagram 3] FIG. 2 is an enlarged view of part A in FIG. 1, showing a schematic diagram of the structure of a main part of a free-standing thin film in the first embodiment. [Figure 4] FIG. 1 is an overall perspective view showing a schematic configuration of a free-standing thin film in a first embodiment. [Diagram 5] FIG. 2 is a process diagram illustrating a method for producing a free-standing thin film in the first embodiment. [Figure 6] FIG. 11 is an overall perspective view showing a schematic configuration of a free-standing thin film in a second embodiment. [Figure 7]FIG. 1 is an enlarged view of part B in FIG. 1, illustrating a schematic structure of a main part of a free-standing thin film in accordance with a second embodiment. [Figure 8] FIG. 11 is a schematic diagram showing the structure of a main part of a free-standing thin film in embodiment 3. [Figure 9] FIG. 2 is an overall configuration diagram of an apparatus used for evaluating the strength of a film in the examples. [Figure 10] FIG. 2 is a diagram showing a schematic structure of a main part of a thin film in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (Embodiment 1) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of a free-standing thin film and a method for manufacturing the same will be described with reference to the drawings. As shown in Figs. 1 to 4, in this embodiment, the free-standing thin film 1 is made of a film of a polycrystalline material 10 composed of crystal particles C of an apatite-type complex oxide. The polycrystalline material 10 can include one or more polycrystalline layers 11 in which a large number of crystal particles C are assembled, and in the configuration example shown in Fig. 1, the polycrystalline layer 11 has a single-layer structure. In the case of a multi-layer structure, as described later, a plurality of polycrystalline layers 11 are laminated in the film thickness direction Z of the free-standing thin film 1 (i.e., the Z-axis direction shown in Fig. 1). Note that the free-standing film refers to a film in which both sides of two film surfaces 21, 22 opposing each other in the film thickness direction Z can exist independently without being supported by a support such as a substrate.
[0015] The polycrystalline layer 11 constituting the free-standing thin film 1 is a dense body in which a large number of crystal grains C are continuously assembled with their grain boundaries C1 in contact with each other in a film plane direction (for example, the X-axis direction or Y-axis direction shown in FIG. 1) perpendicular to the film thickness direction Z. When the free-standing thin film 1 is a single layer film, two particle surfaces of the crystal grains C in the film thickness direction Z are exposed, and adjacent particle surfaces are connected to each other to form two film surfaces 21, 22.
[0016] Each crystal particle C is a thin plate-like particle made of a complex oxide having an apatite-type crystal structure shown in FIG. 2, and it is desirable that the c-axis of the hexagonal apatite is oriented along the film thickness direction Z (see, for example, FIG. 3). The a-axis and b-axis of the apatite are in a plane perpendicular to the c-axis. The polycrystalline layer 11 in which such crystal particles C are aggregated is desirably formed so that the grain boundaries C1 are aligned along the film thickness direction Z and are evenly arranged over the entire film plane, which is considered to have the effect of improving the film strength against stress. Also, the apatite-type complex oxide has oxide ions (O 2- ) has a tendency to be conductive, which is advantageous when the free-standing thin film 1 is used as an oxide ion conductor.
[0017] The free-standing thin film 1 is formed so that its thickness t is in the range of 0.2 μm or more and 5.0 μm or less. As shown in FIG. 4, the thickness t is the thickness of the film made of the polycrystalline body 10, that is, in the case of a single-layer film, the thickness is the thickness of the polycrystalline layer 11, and can be appropriately set so as to obtain the desired film strength and ion conductivity. When the thickness t is 0.2 μm or more, it is possible to maintain it as a free-standing thin film, and when the thickness t is 5.0 μm or less, it is possible to shorten the migration distance of oxide ions and increase ion conductivity. It is preferable that the thickness t is 1.0 μm or more. The thickness t can be calculated as an average thickness based on cross-sectional observation by a transmission electron microscope (TEM), for example.
[0018] The membrane area S of the free-standing thin film 1 is 1.0 cm 2or more, and is formed so that the film surface roughness Rz is 20 nm or less. The film surface roughness Rz (JIS B0601) is the maximum height of a roughness curve in a reference length, and can be measured using a device capable of measuring minute irregularities on the nano-order, such as an atomic force microscope (AFM). By making the film surface roughness Rz 20 nm or less, the irregularities on the film surfaces 21, 22 are reduced, the stress caused by the irregularities is alleviated, and the occurrence of stress concentration points is suppressed, thereby achieving a roughness of 1.0 cm 2 It is believed that it will be possible to maintain a thin film shape of 5.0 μm or less having an area of 15 nm or less. It is preferable that the film surface roughness Rz is about 15 nm or less.
[0019] The upper limit of the membrane area S of the free-standing thin film 1 is not particularly limited, and the membrane area S can be obtained according to the substrate area used in the manufacturing method described later. Therefore, it can be appropriately set according to the application, etc., but from the viewpoint of manufacturing, for example, 500 cm 2 It is desirable to set the range to about 200 cm or less. 2 The membrane area S can be calculated, for example, based on the results of measuring the planar shape with a laser microscope using laser light.
[0020] The detailed structure of the self-supporting thin film 1 in this embodiment will be described below. In FIG. 1, the self-supporting thin film 1 is a single layer film, and the two surfaces of the polycrystalline body 10 (polycrystalline layer 11) facing each other in the film thickness direction Z are film surfaces 21 and 22. The polycrystalline layer 11 is a layer in which at least a part of the crystal grains C of the apatite structure is oriented in one direction, and preferably has a c-axis orientation in which the c-axis direction of the crystal grains C and the film thickness direction Z are approximately aligned. In addition, it is preferable that a grain boundary C1 is formed between adjacent crystal grains C in a direction approximately aligned with the film thickness direction Z. Specifically, when the ratio of the crystal grains C having c-axis orientation among the crystal grains C constituting the polycrystalline layer 11 is defined as the c-axis orientation ratio, the polycrystalline layer 11 in which the c-axis orientation ratio calculated using the Lotgering method is 0.25 or more and the grain boundaries C1 are aligned in the same direction can be an oriented layer.
[0021] When the c-axis orientation rate is 0.25 or more, the c-axes of more crystal grains C are aligned along the film thickness direction Z or are less displaced from the film thickness direction Z throughout the polycrystalline layer 11 (the c-axis direction of the crystal grains C is indicated by the dotted arrow in FIG. 3). At this time, the C-faces of the apatite are easily exposed as the film surfaces 21 and 22, which is preferable from the viewpoint of improving the oxide ion conductivity and film strength. More preferably, the c-axis orientation rate is 0.6 or more as calculated by the Lotgering method. The c-axis orientation rate can be calculated, for example, from the peak intensity in the X-ray diffraction pattern obtained by an X-ray diffractometer using the known Lotgering formula.
[0022] At this time, as shown in FIG. 3, it is desirable that crystal grains C having c-axis orientation are aggregated in the layer cross section of the polycrystalline layer 11, and the direction of the grain boundary C1 appearing in the layer cross section is approximately the same as the film thickness direction Z. In this way, it is considered that the grain boundary C1 has an effect of improving the film strength by being perpendicular (90°) to the film surfaces 21 and 22 or a direction close to that. For this purpose, it is preferable that the grain boundary angle θ is 80° or more when the angle between the direction of the grain boundary C1 appearing in the layer cross section and the direction parallel to the film surfaces 21 and 22 (film plane direction X, Y), in which case the grain boundary angle θ is 80° or more, in other words, the angle (deviation angle) between the direction of the grain boundary C1 and the film thickness direction Z is 10° or less. The grain boundary angle θ (or deviation angle) can be calculated, for example, as the average value of the measured angles of a plurality of grain boundaries C1 based on TEM cross-section observation.
[0023] The average particle diameter (D50) of the crystal particles C observed on the film surfaces 21, 22 is desirably, for example, 5 μm or more and 500 μm or less. If the average particle diameter is less than 5 μm, the grain boundaries C1 formed in the polycrystalline layer 11 will increase, and there is a concern that the grain boundaries C1, which are structural defects, may affect the oxide ion conductivity. If the average particle diameter exceeds 500 μm, the grain boundaries C1 will decrease, and there is a concern that the effect of improving the film strength will be reduced.
[0024] As shown in Fig. 4, the free-standing thin film 1 is a flat film with a large film area S relative to the film thickness t, and it is believed that the even formation of grain boundaries C1 extending in a substantially perpendicular direction between the film surfaces 21, 22 contributes to maintaining the strength of the entire film. In addition, the area of the film surfaces 21, 22 exposed to the atmosphere is larger than in the past, making it easier to form structural defects such as oxygen vacancies. Furthermore, the improvement in the c-axis orientation rate increases the ratio of C-faces in the surfaces exposed to the atmosphere, which acts in a direction that makes it easier to form structural defects, and it is believed that this provides the effects of stress relaxation due to structural defects and improved oxide ion conductivity.
[0025] In this way, it is believed that the free-standing thin film 1 has an increased membrane area S relative to the thickness t, which is advantageous for improving the membrane strength and exhibiting oxide ion conductivity. Alternatively, when the shape of the free-standing thin film 1 shown in Fig. 4 is, for example, approximately square, the ratio of the length of one side, L, to the thickness t (i.e., aspect ratio: L / t) becomes larger, allowing the free-standing thin film 1 to function as a film electrolyte with high ion conductivity and bending modulus. Such a film electrolyte is suitably used in various applications such as electrochemical cells.
[0026] For example, when the thickness t of the freestanding thin film 1 is 5.0 μm, the film area S is 1.0 cm 2 (i.e., if the side length L is 1 cm = 10,000 μm) or more, the aspect ratio will be 2000 (L / t = 10,000 μm / 5 μm) or more. The shape of the free-standing thin film 1 is not limited to a rectangular shape and can be any shape. In this case, the aspect ratio can also be expressed using the side length L of a square with the same area as the membrane area S.
[0027] As the composite oxide having an apatite structure constituting the self-supporting thin film 1, an apatite composite oxide represented by the following formula can be suitably used. Formula: A 10-x B 6-y M y O 27-z However, in the formula, A is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Be, Mg, Ca, Sr, and Ba; B is an element containing Si or Ge or both; M is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Y, Zr, Ta, Nb, B, Ge, Zn, Sn, W, and Mo; x, y, and z are numbers that satisfy the following conditions: -0.5≦x≦2.0, 0.0≦y≦3.0, and -6.0≦z≦4.2.
[0028] The element A in the formula is a lanthanoid or alkaline earth metal that can become a positively charged ion and form an apatite-type hexagonal crystal structure. For example, from the viewpoint of further increasing the oxide ion conductivity, it is preferable to combine it with one or more elements selected from the group consisting of La, Ce, Nd, Ca, Sr, and Ba, and among them, it is preferable to combine it with one of La or Nd, or with one or more elements selected from the group consisting of La and Ce, Nd, Ca, Sr, and Ba. Moreover, the B element in the formula may be an element containing Si or Ge or both.
[0029] The M element in the formula is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Y, Zr, Ta, Nb, B, Ge, Zn, Sn, W, and Mo. For example, from the viewpoint of increasing the oxide ion conductivity, it is preferable to use Al, Ti, Y, Zr, B, and the like.
[0030] In the formula, x is preferably −0.5 or more and 2.0 or less, from the viewpoint of increasing the degree of orientation and oxygen ion conductivity. In the formula, y is preferably 0.0 or more and 3.0 or less from the viewpoint of filling the B element position in the apatite-type crystal lattice. In order to maintain electrical neutrality in the apatite-type crystal lattice, z in the formula is preferably equal to or greater than −6.0 and equal to or less than 4.2.
[0031] As the apatite-type composite oxide represented by the above formula, for example, a rare earth silicate composite oxide in which the element A in the formula is a rare earth element and the element B in the formula is Si can be used. Examples of rare earth silicate composite oxides include La 9.33 S 6.0 O 26 , La 9.33 S 5.3 B 0.7 O 25.65 , La 9.33 S 5.3 Ti 0.7 O 26 , La9.33 S 5.3 Al 0.7 O 25.65 , La 9.33 S 5.3 Y 0.7 O 25.65 , La 9.33 S 5.3 Zr 0.7 O 26 , La 9.00 Ce 0.33 S 6.0 O 26 However, the present invention is not limited to these. In the apatite-type crystal structure shown in FIG. 2, the arrows A, B, and O in the figure indicate the positions occupied by the elements A, B, and O in the formula.
[0032] As shown in Fig. 5, when a free-standing thin film 1 is manufactured using such an apatite-type complex oxide, a method can be adopted in which an amorphous complex oxide film 100, which is an apatite-type complex oxide or its precursor, is formed on a substrate 200, crystallized and oriented, and then separated from the substrate 200. Materials for the substrate 200 include metal materials such as Si and Pt, and oxide materials such as sapphire (Al2O3) and ZrO, and preferably a substrate made of an oxide material can be used. Specifically, as shown below, (1) a first step of forming a first layer 300 made of a composition that is sublimable at the crystallization temperature of an apatite-type composite oxide on the surface of a substrate 200; (2) a second step of forming an amorphous complex oxide film 100 containing the same constituent elements as the apatite-type complex oxide on the surface of the first layer 300; (3) a third step of forming a second layer 400 made of an oxide containing a part of the constituent elements of the apatite-type complex oxide or a precursor thereof on the surface of the amorphous complex oxide film 100; (4) A polycrystalline layer 11 made of an apatite-type complex oxide is formed by heating the amorphous complex oxide film 100 to a temperature equal to or higher than the crystallization temperature thereof and then heat-treating the film. In addition, a fourth step is included in which the first layer 300 is removed by sublimation, thereby producing a free-standing thin film 1.
[0033] The first step is a step of forming a composition layer (hereinafter, the first layer) 300, which is to be removed in the fourth step, on the surface that will become the main surface 200a of the substrate 200 as a method of separating the free-standing thin film 1 in the manufacturing process. The composition forming the first layer 300 may be any composition having a high vapor pressure that can be removed by sublimation during the heat treatment of the amorphous complex oxide film 100, and can crystallize the amorphous complex oxide film 100 into an apatite structure and can peel off the oriented apatite from the substrate 200 after the heat treatment. Examples of compositions with high vapor pressure include bismuth oxide, zinc oxide, boron oxide, sulfur, and phosphorus. From the viewpoint of reducing element diffusion and internal stress during the heat treatment of the apatite, it is preferable to use an oxide composition.
[0034] Examples of methods for forming a composition with a high vapor pressure include atomic layer deposition, ion plating, pulsed laser deposition, plating, sputtering, and vapor deposition. Any film-forming method can be used, such as screen printing or spin coating, of an amorphous oxide prepared by a wet method such as coprecipitation or sol-gel. From the viewpoints of film quality and productivity, it is preferable to select the sputtering method.
[0035] The film formation by sputtering can be performed using an existing sputtering device, and a target made of a composition for forming the first layer 300 and the substrate 200 are placed opposite each other to perform sputtering, thereby forming a film made of a desired composition on the substrate 200. As the substrate 200, an oxide substrate is preferable from the viewpoint of suppressing structural defects such as cracks caused by differences in thermal expansion coefficients during heat treatment in the fourth step described below. For example, a sapphire substrate having a C-plane as the main surface 200a can be used, and it is preferable to form a c-axis oriented film made of a hexagonal material (e.g., ZnO) as the first layer 300 on the main surface 200a from the viewpoint of facilitating c-axis orientation of hexagonal apatite. In addition, the substrate 200 may be preheated and sputtered while being held at a predetermined temperature in the range of 300 to 800°C.
[0036] In the second step, the amorphous complex oxide film 100 can be formed on the surface of the first layer 300 by a similar method, preferably a sputtering method. Specifically, the amorphous complex oxide film 100 can be formed on the substrate 200 by a sputtering method using a target made of a complex oxide having the same constituent elements as the apatite to be produced. The composition of the complex oxide (sintered body) used as the sputtering target can be the same as that of the amorphous complex oxide film 100 to be formed, and a composition obtained by subtracting the amount of the oxide or precursor added in the third step from the composition of the target apatite-type complex oxide can be used.
[0037] Next, in the third step, a second layer 400 made of an oxide or a precursor thereof containing some of the constituent elements of the apatite-type complex oxide is formed on the surface of the amorphous complex oxide film 100 on the substrate 200. The oxide or the precursor thereof contains one or more of the elements A, B, and M that constitute apatite. The film formation method can be the same as that of the above step, and preferably, a sputtering method can be used.
[0038] In the first to third steps, when a sputtering method is adopted, a radio frequency (RF) sputtering method is preferably used. This allows the use of an oxide target that is a high resistance body. Specifically, a replacement gas is introduced into a vacuum chamber in which a sputtering target and a substrate 200 (opposing electrode) are placed, and the pressure in the chamber is maintained at a predetermined pressure. In this state, a radio frequency voltage is applied between the electrodes to perform plasma processing. The degree of vacuum in the vacuum chamber is, for example, 1×10 -5 More than 1×10 -2 The pressure of the plasma treatment can be in the range of 0.5 Pa or more and 30 Pa or less. In addition, inert gases such as Ar, He, Ne, Kr, Xe, and Rn are used as replacement gases, and reactive sputtering can also be performed using gases such as O2 and N2.
[0039] From the viewpoint of improving the film density, it is preferable to introduce O2 gas into the chamber during film formation. By introducing O2 gas, it is possible to suppress the occurrence of large structural defects such as voids in the film to be formed, and a more suitable film can be formed when applied to a highly active cell used in, for example, a solid oxide fuel cell (SOFC). It is preferable to select the ratio of O2 gas in the atmosphere in the range of 5% to 20%. If the ratio of O2 gas is less than 5%, the effect of suppressing the occurrence of voids and the like may be insufficient, and if the ratio is higher than 20%, the rate of formation of the amorphous complex oxide film 100 formed on the substrate 200 may be slowed down, and the manufacturing efficiency may be reduced.
[0040] The power density during plasma processing is, for example, 1.0 to 4.0 W / cm 2 The power is selected within the following range, and it is possible to efficiently form a film while preventing abnormal deposition and sparks. Preferably, it is 1.5 W / cm 2 More than 3.0W / cm 2 The following range is preferable. The method for producing the sputtering target is not particularly limited, and for example, a method in which raw materials for the composition to be the target are mixed and fired to form a sintered body, such as the method described in Patent Document 1, can be used.
[0041] Thereafter, in a fourth step, the amorphous complex oxide film 100 on the substrate 200 and the second layer 400 formed on its surface are further heat-treated. This allows the amorphous complex oxide film 100 and the second layer 400 to be integrated and crystallized into an apatite structure and oriented to form a polycrystalline layer 11 made of an apatite-type complex oxide. The formed polycrystalline layer 11 can then be separated from the substrate 200 to form a free-standing thin film 1.
[0042] The temperature of the heat treatment is preferably 800°C or higher, more preferably 850°C or higher and 1200°C or lower, more preferably 900°C or higher and 1100°C or lower, in terms of the efficiency of crystallizing the amorphous complex oxide film 100 into an apatite structure. The complex oxide film formed by the sputtering method is obtained as an amorphous material and is crystallized by heat treatment, but a long time is required to advance the crystallization at temperatures below 800°C. In addition, when the heat treatment furnace is a muffle furnace, it is not easy to set the temperature to more than 1200°C, and generally, a heating furnace that can be set to a temperature of more than 1200°C is expensive, so it is not practically advantageous.
[0043] During this heat treatment, in the process in which the second layer 400 formed on the surface layer of the amorphous complex oxide film 100 diffuses into the amorphous complex oxide film 100, a large number of grain boundaries C1 extending in a direction perpendicular to the film plane direction are formed, which is thought to improve the film strength and the c-axis orientation rate of the crystal grains C. In addition, the first layer 300 formed on the substrate 200 is removed by sublimation, and the polycrystalline layer 11 that becomes the free-standing thin film 1 can be separated from the substrate 200.
[0044] The atmosphere for the heat treatment can be an air atmosphere. The heat treatment for peeling off from the substrate 200 can be performed in the same temperature range as the heat treatment for crystallizing the amorphous complex oxide film 100 into an apatite structure, but can be performed more efficiently by flowing the above-mentioned inert gas or reducing gas such as hydrogen. Preferably, the heat treatment is performed in an air atmosphere for a sufficient time to crystallize into an apatite structure, and then the atmosphere is replaced with a reducing gas atmosphere to perform the heat treatment, thereby efficiently producing the free-standing thin film 1.
[0045] The method of making the oriented apatite-type complex oxide film into the free-standing thin film 1 by the heat treatment in the fourth step is not limited to the method of separating the oriented apatite-type complex oxide film from the substrate 200 using a composition with a high vapor pressure as in the first and fourth steps described above, and any method can be adopted. For example, there is a method in which a composition with high solubility is used as the substrate 200, an oriented apatite-type complex oxide film is produced as in the second to fourth steps, and then the substrate 200 is removed by dissolving in water or the like to obtain the free-standing thin film 1 consisting of the polycrystalline layer 11. The composition with high solubility is not particularly limited, but it is preferable to use an oxide composition from the viewpoint of reducing diffusion and internal stress during heat treatment of apatite. Examples of such oxide compositions with high solubility include strontium chromate and strontium aluminate.
[0046] (Embodiment 2) A second embodiment of the free-standing thin film will be described with reference to the drawings. As shown in Fig. 6 and Fig. 7, the free-standing thin film 1 can have a multi-layer structure in which the polycrystalline layer 11 constituting the polycrystalline body 10 has two or more layers. In that case, it is desirable that at least one layer of the polycrystalline layer 11 constituting the polycrystalline body 10 is an oriented layer having c-axis orientation and aligned grain boundaries C1, and in this embodiment, a two-layer structure having two oriented layers is used. The following description will focus on the differences from the first embodiment. In addition, among the symbols used in the second and subsequent embodiments, the same symbols as those used in the previous embodiments represent the same components, etc. as those in the previous embodiments, unless otherwise specified.
[0047] 6 and 7, the free-standing thin film 1 is configured such that a polycrystalline layer 11A and a polycrystalline layer 11B having the same structure are laminated in the film thickness direction Z between two opposing film surfaces 21 and 22, so that the overall film thickness t, film area S, and surface roughness Rz are within the above-mentioned ranges. The exposed surfaces of the polycrystalline layer 11A and the exposed surfaces of the polycrystalline layer 11B form film surfaces 21 and 22, respectively, and a layer interface 3 is formed between the polycrystalline layer 11A and the polycrystalline layer 11B. Both the polycrystalline layer 11A and the polycrystalline layer 11B are oriented layers, and are formed to have the same layer thickness here, but may have different layer thicknesses.
[0048] In this way, the polycrystalline body 10 that becomes the free-standing thin film 1 has a layer interface 3, and the crystal grains C of the two polycrystalline layers 11A, 11B are configured to contact each other at their grain boundaries in the film thickness direction Z, thereby acting in the same way as the grain boundary C1 in the film plane direction, thereby obtaining the effect of further improving the film strength.
[0049] The free-standing thin film 1 is not limited to a two-layer structure, but may be configured by stacking three or more polycrystalline layers 11. In that case, layer interfaces 3 are formed between each of the polycrystalline layers 11, resulting in a plurality of layer interfaces 3. The number of layers can be set arbitrarily within a predetermined film thickness range, and the effect of the formation of the layer interfaces 3 on the oxide ion conductivity is considered to be small, but from the viewpoint of manufacturing, it is preferable to have, for example, about five layers or less.
[0050] (Embodiment 3) A third embodiment of the self-supporting thin film will be described with reference to the drawings. As shown in FIG. 8, when the self-supporting thin film 1 has a multi-layer structure, it can also have a structure including two or three or more polycrystalline layers 11 having different layer thicknesses and c-axis orientation rates. The upper diagram of FIG. 8 shows a two-layer structure in which a polycrystalline layer 11C serving as a random grain boundary layer is disposed on the surface layer of the polycrystalline layer 11 in the first embodiment. As shown in the lower diagram of FIG. 8, the polycrystalline layer 11C can also be disposed between the polycrystalline layer 11A and the polycrystalline layer 11B in the second embodiment to form a three-layer structure. The following mainly describes the differences from the first and second embodiments.
[0051] In the upper diagram of FIG. 8, the polycrystalline body 10 that becomes the freestanding thin film 1 is configured such that a polycrystalline layer 11C, which is a grain boundary random layer, is laminated in the film thickness direction Z on one surface of a polycrystalline layer 11, which is an oriented layer having c-axis orientation and aligned grain boundaries C1, so that the total film thickness t, film area S, and surface roughness Rz of the film surfaces 21 and 22 are within the above-mentioned ranges. The polycrystalline layer 11C is a layer in which the grain boundary angle θ shown in FIG. 3 is less than 80° and the deviation angle is greater than 10°, and the grain boundaries C1 are oriented in an arbitrary direction (random direction), in other words, the grain boundaries C1 are not aligned. The c-axis orientation of the grain boundary random layer is not particularly limited, and the c-axis orientation ratio according to the Lotgering method may be 0.25 or more or less than 0.25. Preferably, from the viewpoint of oxide ion conductivity, the c-axis orientation ratio is 0.25 or more.
[0052] In order to suppress the influence of the grain boundary random layer on the oxide ion conductivity and the surface unevenness, it is desirable to form the layer thickness t2 of the polycrystalline layer 11C that becomes the grain boundary random layer to be sufficiently thinner than the layer thickness t1 of the polycrystalline layer 11 that becomes the oriented layer. If the stress concentration due to the surface unevenness is not apparent, the effect of stress relaxation by the grain boundaries is highly obtained, and it is considered that it effectively acts to improve the film strength together with the layer interface 3 in the film thickness direction Z. It can be preferably about 1 / 50 or less, more preferably about 1 / 100 or less, of the layer thickness t1 of the polycrystalline layer 11. For example, by forming the polycrystalline layer 11C with a layer thickness t2 of 0.05 μm (50 nm) on the surface layer of the polycrystalline layer 11 with a layer thickness t1 of about 5 μm, it is possible to improve the film strength while suppressing the stress concentration.
[0053] As shown in the lower diagram of FIG. 8, when the free-standing thin film 1 has a three-layer structure, the polycrystalline layer 11A and the polycrystalline layer 11B, which are oriented layers, are laminated in the film thickness direction Z, sandwiching the polycrystalline layer 11C, which is a random grain boundary layer. The total film thickness t, the film area S, and the surface roughness Rz of the film surfaces 21 and 22 are configured to be within the above-mentioned ranges. The free-standing thin film 1 can also be configured to have a plurality of polycrystalline layers 11C, which are random grain boundary layers. In that case, for example, the random grain boundary layers and the oriented layers are configured to be alternately arranged, thereby improving the strength of the entire film. Such a free-standing thin film 1 has excellent processability, and can be applied to various uses by processing it into a shape other than a flat shape, such as a curved or cylindrical shape. EXAMPLES
[0054] Example 1 A free-standing thin film 1 having the same structure as that of the above-mentioned embodiment 1 was produced and evaluated. The free-standing thin film 1 made of the polycrystalline material 10 having an oriented apatite structure was produced based on the method shown in Fig. 5 above, and an oriented ZnO layer, which is the first layer 300, was formed on a substrate 200 by high-frequency sputtering (first step), and then an amorphous composite oxide film 100 having an apatite composition and an amorphous SiO2 layer, which is the second layer 400, were formed (second and third steps), followed by heat treatment (fourth step). The specific method is shown below.
[0055] <Preparation of free-standing thin film 1> First, a sapphire substrate 200 and a sputtering target made of ZnO were placed facing each other in a chamber of a known high-frequency sputtering device, and the vacuum level was set to 1×10 -4 The chamber was evacuated until the pressure was below 1.0 Pa. Ar gas was introduced into the chamber and maintained at 1.0 Pa. The high-frequency power supply was operated to supply high-frequency power. The substrate 200 was a square substrate (10 mm x 10 mm x 1.0 mm) using hexagonal sapphire C-face. The high-frequency power was 400 W and the deposition time was 30 minutes to deposit ZnO with its c-axis oriented perpendicular to the substrate plane. The thickness of the ZnO layer was 300 nm.
[0056] Next, the substrate 200 on which the ZnO layer was formed and a rare earth silicate-based apatite composition (La 9.33 S 5.8 O 25.6 The sputtering target was placed facing each other in a chamber, and the vacuum level was set to 1×10 -4 After evacuating the chamber to below 1.0 Pa, Ar gas mixed with 10% O was introduced. With the pressure inside the chamber maintained at 1.0 Pa, a high-frequency power of 500 W (2.73 W / cm 2 ) and a film formation time of 600 minutes, an amorphous composite oxide film 100 having an apatite composition was formed on the ZnO layer.
[0057] Thereafter, the substrate 200 on which the amorphous complex oxide film 100 and the ZnO layer were formed and a sputtering target made of SiO2 were placed facing each other in a chamber, and the vacuum level was set to 1×10 -4 After evacuating the chamber to a pressure of 1.0 Pa or less, Ar gas was introduced. With the pressure inside the chamber maintained at 1.0 Pa, a high-frequency power of 500 W (2.73 W / cm 2 ) and a deposition time of 1 minute, an amorphous SiO2 layer was formed on the amorphous complex oxide film 100.
[0058] The film-substrate composite thus obtained was heat-treated at 1000°C to crystallize the amorphous composite oxide film 100 into apatite and impart orientation, and the ZnO layer was sublimated and removed, and then separated from the substrate 200. The heat treatment was performed by raising the temperature to 1000°C in an air atmosphere over 5 hours, holding the temperature for 4 hours, and then introducing 4% H2 mixed N2 gas over 100 minutes to completely replace the air atmosphere. After holding the temperature in this state for 10 hours, the temperature was lowered to room temperature over 2 hours to obtain a free-standing thin film 1 having an oriented apatite structure.
[0059] <Evaluation of free-standing thin film 1> The obtained free-standing thin film 1 was subjected to X-ray diffraction pattern analysis by X-ray diffraction method and elemental analysis by ICP emission spectrometry. In addition, the film shape and sample cross section were observed by various microscopes. Specifically, the surface roughness was measured by an atomic force microscope (AFM), the planar shape was measured by a laser microscope, and the structure in the cross-sectional direction was analyzed by a transmission electron microscope (TEM). These results are shown in Table 1 as Example 1.
[0060] As shown in Table 1 as the film structure (parent phase), the obtained free-standing thin film 1 was composed of La 9.33 S 6.0 O 26 It was confirmed that the film was made of polycrystals 10 in which crystals C having an apatite structure having a composition of 1.0 cm2. The film thickness t was 5.0 um and the film area S was 1.0 cm2. 2 It was confirmed that the film was a single layer consisting of a polycrystalline layer 11 (oriented layer) of oriented apatite with a film surface roughness Rz of 15 nm, a c-axis orientation rate of 0.25, and a grain boundary angle θ of 80°, and that it had no layer interface 3 in the film thickness direction Z. The apparatus used for these measurements is shown below. X-ray diffraction equipment: Rigaku Corporation, SmartLab -ICP emission spectrometer: Shimadzu Corporation, ICPS-7510 Laser microscope: Olympus Corporation, LEXT OLS4100 Transmission electron microscope: GRAND-ARM300, manufactured by JEOL Ltd.
[0061] The film thickness t in Table 1 is a calculated value based on a TEM image of a cross-sectional sample, and is the arithmetic average value of film thicknesses measured at 40 arbitrary points in a 10 μm long range along the film plane. The c-axis orientation rate is a ratio calculated by measuring the X-ray diffraction patterns of 40 arbitrary particles in the cross-sectional TEM observation and using the Lotgering method, and the grain boundary angle θ is the arithmetic average value calculated by measuring the angles of 40 arbitrary grain boundaries C1 in the cross-sectional TEM observation.
[0062] [Table 1]
[0063] Next, Pt films were formed by vapor deposition on two film surfaces 21 and 22 facing each other in the film thickness direction Z of the obtained free-standing thin film 1, and Pt leads were then connected to each film to measure the oxide ion conductivity [log(S / cm)] based on the complex impedance method. The apparatus and measurement conditions used for the measurement are shown below. The measurement results are shown in Table 2. Equipment used: ModuLab XM ECS, manufactured by Hokuto Denko Corporation Applied voltage: 0V Measurement amplitude: 10mV Measurement frequency: 1MHz~0.1Hz Measurement environment: 500℃ air (oxygen concentration 20.9%)
[0064] Furthermore, the strength of the obtained free-standing thin film 1 was measured using an apparatus shown in Fig. 9. In Fig. 9, a jig 501 and an upper plate balance 502 are placed on a base 500, and the free-standing thin film 1 serving as an evaluation sample is supported on the tip side of an arm 503 provided on the upper end of the ceramic jig 501. The free-standing thin film 1 is disposed between a pair of arms 503a, 503b extending parallel to the base 500, and is located above one plate 504 of the upper plate balance 502. An arbitrary weight 506 can be placed on the other plate 505 of the upper plate balance 502.
[0065] As shown in an enlarged view of the configuration of the sample evaluation section in FIG. 9, a protrusion 507 that abuts against the lower surface of the free-standing thin film 1 is provided on the lower arm 503b, allowing a load to be applied by a weight 506. An opening 503c is provided on the upper arm 503a above the protrusion 507, allowing a laser microscope 508 to measure the strain that occurs in the free-standing thin film 1 when a load is applied. The same device as the laser microscope used to measure the planar shape described above was used to measure the strain. The flexural modulus (unit: GPa) and flexural strength (unit: MPa) measured using this device are also shown in Table 2.
[0066] [Table 2]
[0067] As shown in Table 2, the obtained free-standing thin film 1 had an oxide ion conductivity of -4.7 [log(S / cm)], a flexural modulus of 78 GPa, and a flexural strength of 110 MPa, all of which were good results.
[0068] (Examples 2 to 7) A free-standing thin film 1 having a different apatite composition was produced by the same manufacturing method as in Example 1. Specifically, in the same manner, when forming an amorphous composite oxide film 100 having an apatite composition on a substrate 200 on which a ZnO layer was formed, the apatite composition used as a sputtering target was La 9.33 S 5.3 B 0.7 O 25.65 Except for that, a free-standing thin film 1 was produced in the same manner as above, and the evaluation results are shown in Tables 1 and 2 as Example 2.
[0069] Furthermore, the rare earth silicate-based apatite composition used as the sputtering target was changed as follows to give Examples 3 to 7. In the same manner, a free-standing thin film 1 was produced and evaluated. The results are shown in Table 1. Example 3: La 9.33 S 5.3 Ti 0.7 O 26 Example 4: La 9.33 S 5.3 Al 0.7 O 25.65 Example 5: La 9.33 S 5.3 Y 0.7 O 25.65 Example 6: La 9.33 S 5.3 Zr 0.7 O 26 Example 7: La 9.00 Ce 0.33 S 6.0 O 26
[0070] As shown in Table 1, it was confirmed that Examples 2 to 7, which used an apatite-type composite oxide containing an M element (Al, Ti, Y, Zr, or B) represented by the above formula, or an apatite-type composite oxide containing two A elements (La, Ce), were also single-layer films of oriented apatite having a film structure similar to that of Example 1. Furthermore, as shown in Table 2, the freestanding thin films 1 of Examples 2 to 7 had oxide ion conductivities of -4.0 to -4.6 [log(S / cm)], which were equal to or greater than that of Example 1, and had flexural moduli of 72 to 79 GPa and flexural strengths of 107 to 110 MPa, all of which showed good film properties.
[0071] Example 8 In the same manufacturing method as in Example 1, the film formation conditions were changed to produce a free-standing thin film 1 of an apatite composition. Specifically, a ZnO layer was formed on the substrate 200, and the apatite composition (La 9.33 S 5.8 O 25.6 ) was used as a sputtering target, and the deposition time for depositing the amorphous complex oxide film 100 was changed to 24 minutes. Furthermore, the deposition time for depositing the amorphous SiO2 layer was changed to 2.4 seconds, but otherwise, a free-standing thin film 1 was produced in the same manner. This was designated Example 8, and the results of evaluation carried out in the same manner are shown in Tables 1 and 2.
[0072] As shown in Table 1, the obtained freestanding thin film 1 was confirmed to be a single layer of oriented apatite having a film thickness t of 0.2 um, which was thinner than that of Example 1, and a film area S and c-axis orientation equivalent to those of Example 1. Furthermore, as shown in Table 2, the oxide ion conductivity was -4.6 [log(S / cm)], which was equal to or greater than that of Example 1, and the flexural modulus was 78 GPa and the flexural strength was 110 MPa, all of which were good film properties.
[0073] Example 9 In the same manufacturing method as in Example 1, a free-standing thin film 1 of apatite composition was produced by changing the layer formed on the substrate 200. Specifically, when forming the first layer 300 in contact with the substrate 200, SiO2 was used as the sputtering target instead of ZnO, and otherwise the substrate 200 on which an oriented SiO2 layer was formed was produced in the same manner. Furthermore, when forming the amorphous complex oxide film 100, the apatite composition used as the sputtering target was changed to La 9.33 S 5.6 O 25.2 A free-standing thin film 1 was produced in the same manner, except for the above changes. This was designated Example 9, and the results of evaluation carried out in the same manner are shown in Tables 1 and 2.
[0074] As shown in Table 1, the obtained free-standing thin film 1 has the same film thickness t and film area S as Example 1, and the surface roughness Rz is reduced to 8 nm, and the c-axis orientation rate is 0.6, and the grain boundary angle θ is 88°, confirming that it is a single layer of oriented apatite with improved c-axis orientation. Also, as shown in Table 2, the oxide ion conductivity is -2.5 [log (S / cm)], which exceeds -4.0 [log (S / cm)], and is greatly improved compared to the case where a ZnO layer is used. Furthermore, the flexural modulus is reduced to 68 GPa, or less than 70 GPa, and the flexural strength is 116 MPa, both of which are better film properties than the case where a ZnO layer is used.
[0075] Example 10 In the same manufacturing method as in Example 1, the film formation conditions were changed to produce a self-supporting thin film 1 having an apatite composition with a multi-layer structure as shown in the embodiment 2. Specifically, an apatite composition (La 9.33 S 5.8 O 25.6 ) was used as a sputtering target to form the amorphous complex oxide film 100, the film formation time was changed to 300 minutes, and the film formation time for forming the amorphous SiO2 layer thereon was changed to 0.5 minutes. Next, a heat treatment was performed in the same manner, and the temperature was raised to 1000°C in an air atmosphere over 5 hours, held at that temperature for 4 hours, and then lowered to room temperature over 2 hours.
[0076] In this way, a layer of oriented apatite integrated on the substrate 200 was formed, and then an amorphous composite oxide film 100 was formed on the surface of the substrate 200 for 300 minutes in the same manner, and an amorphous SiO2 layer was formed on the amorphous composite oxide film 100 for 0.5 minutes. Next, the same heat treatment as described above was performed, and the temperature was raised to 1000°C in an air atmosphere over 5 hours and held for 4 hours. Thereafter, in the same manner as in Example 1, 4% H2 mixed N2 gas was introduced to replace the air atmosphere, and the atmosphere was held for 10 hours, and then the temperature was lowered to room temperature over 2 hours to obtain a free-standing thin film 1. This is Example 10, and the results of the evaluation performed in the same manner are shown in Tables 1 and 2.
[0077] As shown in Table 1, the obtained free-standing thin film 1 had a film thickness t and a film area S equivalent to those of Example 1, a surface roughness Rz of 20 nm, and was confirmed to be a multilayer film in which two oriented apatite layers were laminated with a layer interface 3 in between. Furthermore, as shown in Table 2, the bending strength was 121 MPa, which was higher than that of a single layer film, and the bending modulus was 78 GPa and the oxide ion conductivity was -4.8 [log(S / cm)], indicating that good film properties were obtained.
[0078] Example 11 In the same manufacturing method as in Example 10, the film formation conditions were changed to produce a self-supporting thin film 1 having the multi-layer structure of the apatite composition shown in the third embodiment. Specifically, a ZnO layer was formed on the substrate 200, and the apatite composition (La 9.33 S 5.8 O 25.6 ) was used as a sputtering target, the deposition time for forming the first amorphous complex oxide film 100 was changed to 594 minutes, and the deposition time for forming the amorphous SiO2 layer thereon was changed to 1 minute. In addition, when forming the second amorphous complex oxide film 100, the apatite composition serving as the sputtering target was changed to La 9.33 S 6.0 O 26The temperature was changed to 100° C., and the film was formed for 6 minutes, and then the same heat treatment was performed without forming an amorphous SiO2 layer. A free-standing thin film 1 was produced by the same method as above. This was designated as Example 11, and the results of the evaluation performed in the same manner are shown in Tables 1 and 2.
[0079] As shown in Table 1, the obtained free-standing thin film 1 was confirmed to have a film thickness t and a film area S equivalent to those of Example 1, a surface roughness Rz of 14 nm, and a multilayer film in which a grain boundary random layer having a layer thickness t2 of 0.05 μm was laminated on the surface layer of an orientation layer (parent phase) having a layer thickness t1 of 4.95 μm. Specifically, the orientation layer had a c-axis orientation ratio of 0.25 and a grain boundary angle θ of 80°, and the grain boundary random layer had a c-axis orientation ratio of 0.25 and a grain boundary angle θ of 45°.
[0080] Furthermore, as shown in Table 2, the obtained free-standing thin film 1 had a bending strength of 125 MPa, which was higher than that of the multilayer film of Example 10, and had an oxide ion conductivity of -4.9 [log(S / cm)] and a bending modulus of 79 GPa, thereby obtaining favorable film properties.
[0081] Example 12 A self-supporting thin film 1 having a similar multilayer structure was produced by changing the film formation conditions in the same manufacturing method as in Example 11. Specifically, the layer formed on the substrate 200 was the same SiO2 layer as in Example 9, and when forming the first amorphous complex oxide film 100, the apatite composition serving as the sputtering target was changed to La 9.33 S 5.6 O 25.2 Except for this, the first and second amorphous complex oxide films 100 were formed in the same manner to prepare a free-standing thin film 1. This was designated as Example 12, and the results of evaluation carried out in the same manner are shown in Tables 1 and 2.
[0082] As shown in Table 1, the obtained free-standing thin film 1 was confirmed to be a multilayer film having a surface roughness Rz of 9 nm, in which a grain boundary random layer having a layer thickness t2 of 0.05 μm was laminated on the surface layer of an oriented layer (parent phase) having a layer thickness t1 of 4.95 μm, as in Example 11. Specifically, the oriented layer had a c-axis orientation ratio of 0.6 and a grain boundary angle θ of 88°, and the grain boundary random layer had a c-axis orientation ratio of 0.25 and a grain boundary angle θ of 45°.
[0083] Furthermore, as shown in Table 2, the obtained freestanding thin film 1 had an oxide ion conductivity of -3.1 [log(S / cm)] and a flexural modulus of 70 GPa, which were improved to approximately the same level as in Example 9, and also had a flexural strength of 128 MPa, which was higher than that of the multilayer film of Example 11, and thus good film properties were obtained.
[0084] Comparative Example 1 For comparison, a thin film having an apatite composition was produced by changing the film formation conditions in the same manufacturing method as in Example 1. Specifically, when forming an amorphous complex oxide film 100 on a substrate 200 on which a ZnO layer was formed, the apatite composition serving as a sputtering target was changed to La 9.33 S 6.0 O 26 The film was formed for 600 minutes. After that, the film was formed and heat-treated in the same manner as above, except that the amorphous SiO2 layer was not formed and heat-treated, to produce a thin film. This was used as Comparative Example 1, and the results of the evaluation were also shown in Tables 1 and 2.
[0085] As shown in Table 1, the thin film obtained under the film formation conditions of Comparative Example 1 had a film thickness t of 5 μm and a film area S of 0.25 cm 2 and the area of the substrate 200 (1.0 cm 2) was smaller than that of the free-standing thin film 1 of Examples 1 to 12. The surface roughness Rz was 30 nm, which was larger than that of the free-standing thin film 1 of Examples 1 to 12, and the c-axis orientation ratio was 0.25 and the grain boundary angle θ was 45°, confirming that the grain boundaries C1 of the film were not aligned but oriented in random directions. As shown in Table 2, the flexural modulus was 79 GPa, which was almost the same as that of the free-standing thin film 1 of Examples 1 to 12, but the oxide ion conductivity was -5.5 [log(S / cm)] and the flexural strength was 101 MPa, both of which were lower than those of the free-standing thin film 1 of Examples 1 to 12.
[0086] FIG. 10 is a schematic diagram showing the structure of a thin film obtained by the method shown in Comparative Example 1 as Comparative Example 1. In Comparative Example 1, unlike Examples 1 to 12, the amorphous SiO2 layer, which is the second layer 400, is not formed on the surface layer of the amorphous complex oxide film 100, so it is difficult to control the orientation of the crystal grains C. As a result, the direction of the grain boundaries C1 is easily shifted from the film thickness direction Z, and the crystal grains C are easily aggregated in random directions to form a polycrystalline body 10. In that case, the surface unevenness becomes large on the film surface 21 opposite to the substrate 200, and the film strength decreases due to stress concentration, making it difficult to maintain a film shape of a wide area equivalent to that of the substrate 200.
[0087] In contrast, the free-standing thin film 1 obtained in Examples 1 to 12 is a free-standing thin film having a larger area than that of Comparative Example 1, which is equivalent to the substrate 200, and has high oxide ion conductivity and film strength. Therefore, by using such a free-standing thin film 1 as an electrolyte and forming a cathode and an anode on both surfaces, a high-performance electrochemical cell can be obtained and used in fuel cells, etc., to improve their performance.
[0088] The present invention is not limited to the above-mentioned embodiments, and can be applied to various embodiments without departing from the gist of the present invention. Furthermore, the obtained free-standing thin film 1 can be applied to any purpose, not limited to electrochemical cells for fuel cells. [Explanation of symbols]
[0089] 1 Self-supporting film 10 Polycrystal 11, 11A, 11B, 11C Polycrystalline layer 21, 22 Film surface 3 Layer interface C Crystal particle C1 Grain boundary
Claims
1. A self-supporting thin film (1) composed of an apatite-type complex oxide, The apatite-type composite oxide has one or more polycrystalline layers (11) in a film thickness direction (Z) in which crystal particles (C) of the apatite-type composite oxide are aggregated in a film plane direction (X, Y) with grain boundaries (C1) in contact with each other, The film thickness t is 0.2 μm or more and 5.0 μm or less, and the film area S is 1.0 cm 2 and a film surface roughness Rz of 20 nm or less.
2. 2. The free-standing thin film of claim 1, wherein at least one of the polycrystalline layers is an oriented layer having a c-axis orientation rate in the film thickness direction of 0.25 or more as calculated by the Lotgering method, and the grain boundaries are aligned in the film thickness direction.
3. The free-standing thin film according to claim 2 , wherein the orientation layer is a plurality of layers stacked in the film thickness direction.
4. At least one of the polycrystalline layers is a random grain boundary layer in which the grain boundaries are oriented in a random direction, 4. The free-standing thin film according to claim 2, wherein the orientation layer and the grain boundary random layer are laminated in the thickness direction.
5. 5. The free-standing thin film according to claim 4, wherein a thickness t1 of the orientation layer and a thickness t2 of the grain boundary random layer satisfy the relationship t1>t2.
6. 6. The free-standing thin film according to claim 2, wherein the orientation layer has a c-axis orientation rate of 0.6 or more as calculated by the Lotgering method.
7. 7. The free-standing thin film according to claim 2, wherein in the oriented layer, an angle between the direction of the grain boundaries of the crystal grains appearing in a layer cross section and the film thickness direction is 10° or less.
8. The self-supporting thin film according to any one of claims 1 to 7, wherein the apatite-type complex oxide is represented by the following formula: Formula: A 10-x B 6-y M y O 27-z However, in the formula, A is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Be, Mg, Ca, Sr, and Ba; B is an element containing Si or Ge or both; M is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Y, Zr, Ta, Nb, B, Ge, Zn, Sn, W, and Mo; x, y, and z are numbers that satisfy the following conditions: -0.5≦x≦2.0, 0.0≦y≦3.0, and -6.0≦z≦4.
2.
9. A method for producing a free-standing thin film according to any one of claims 1 to 8, comprising the steps of: forming a first layer (300) made of a composition that can be sublimated at the crystallization temperature of the apatite-type composite oxide on the surface of the substrate (200); forming an amorphous complex oxide film (100) containing the same constituent elements as the apatite-type complex oxide on the surface of the layer of the composition; forming a second layer (400) made of an oxide or a precursor thereof containing a part of the constituent elements of the apatite-type complex oxide on the surface of the amorphous complex oxide film; and a step of heating the amorphous complex oxide film to a temperature equal to or higher than the crystallization temperature thereof to form a polycrystalline layer made of the apatite-type complex oxide, and removing the first layer by sublimation.
Citation Information
Patent Citations
Confirmation of pack drain left under ground in soft ground pack drain work and pack drain material therefor
JP1985088715A
Complex oxide film and production method thereof
JP2013064194A
Metal support-type electrolyte-electrode assembly and manufacturing method thereof
JP2013065518A
Apatite type lanthanum silicogermanate polycrystalline substance and production method therefor, and oxide ionic conductor and solid electrolyte
JP2013184862A
Oxygen sensor element for exhaust gas
JP2021063751A